Plant Pest Impact Metric System (PPIMS): Framework and guidelines for a common set of metrics to classify and prioritise plant pests. (February 2020) - Ireland, Kylie B.; van Klinken, Rieks; Cook, David C.; Logan, David; Jamieson, Lisa; Tyson, Joy L.; Hulme, Philip E.; Worner, Susan; Brockerhoff, Eckehard G.; Fletcher, John D.; Rodoni, Brendan; Christopher, Mandy; et al.
Abstract: Agricultural stakeholders need a common set of metrics to evaluate plant pest impacts to facilitate transparency and harmonisation of pest management and prioritisation across spatial scales and jurisdictions. We propose a classification system that articulates, defines and classifies the magnitude of impacts (historical, current or potential) of pest species (alien and native) in plant production systems. Metrics were identified and criteria defined through consideration of economic parameters, risk assessment standards and guidance tools, discussions with pest risk assessment practitioners and recent advances in environmental impact classification schemes. Twenty metrics were identified and assigned to one of four key metric types: spatiotemporal, market-driven, primary response and mid-to long-term response. Host crop value, Market access, Feasibility of management and Reversibility were identified as disruptor metrics, likely to influence overall classification by at least twice that of other metrics. Application of the system found it was able to classify well-known pests by importance, capturing changes in impact status as the management programme progressed for one pest, and how it was influenced by the geographic scale of assessment for another. Our work demonstrates the value of integrating plant protection science with invasion biology to derive a comprehensive measure of pest impact in agroecosystems that can be utilised by all plant biosecurity stakeholders. Graphical abstract: Image 1 Highlights: A generalised classification and scoring system for plant pest impacts is proposed. 20 metrics: predominantly measurable, economic impacts. Disruptors: crop value, market access, feasibility of management and reversibility. Can be applied across taxonomic, spatio-temporal and jurisdictional boundaries. For scientifically robust, defensible plant pest classification and prioritisation.